2023
DOI: 10.1002/advs.202301053
|View full text |Cite
|
Sign up to set email alerts
|

Achieving Diamond‐Like Wear in Ta‐Rich Metallic Glasses

Abstract: Most metals and alloys suffer from high friction and wear due to their low hardness and lack of self-lubrication. Although plenty of strategies have been proposed, it is still a long-standing challenge to achieve diamond-like wear in metals. Metallic glasses (MGs) are supposed to possess low coefficient of friction (COF) because of their high hardness and fast surface mobility. However, their wear rate is larger than that of diamond-like materials. Here, this work reports the discovery of Ta-rich MGs that exhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 97 publications
(196 reference statements)
0
1
0
Order By: Relevance
“…6a). 54 Ma et al studied the mechanical properties of composite materials with different mass ratios after bonding and found that the trend of changes was very pronounced (Fig. 6b).…”
Section: Excellent Properties Of Amorphous Materialsmentioning
confidence: 99%
“…6a). 54 Ma et al studied the mechanical properties of composite materials with different mass ratios after bonding and found that the trend of changes was very pronounced (Fig. 6b).…”
Section: Excellent Properties Of Amorphous Materialsmentioning
confidence: 99%